Scientific evidence on the modulation of the gut microbiota in food allergies (Research, Society and Development, 2022)
Objective: to verify in the literature relevant publications that allow a greater understanding of how the modulation of the intestinal microbiota through the diet has its role in the prevention and treatment of food allergies. Methodology: narrative review of the literature carried out through a bibliographic search of articles available in the SciELO, Google Scholar, PubMed, Medline and Lilacs databases. Articles available in full and without publication deadline were included. For the survey, the descriptors were used: "intestinal microbiota", "dysbiosis" and "food allergies", in Portuguese, English and Spanish registered in the Descriptors in Health Sciences (DeCS) and according to the Medical Subject Headings (MeSH), also considering the use of the Boolean operator “AND” allowing the combination of the terms, “intestinal microbiota” and “food allergies”, “dysbiosis” and “food hypersensitivities”. Results: The link between microbiome and allergic diseases has grown in recent years and new data supporting a link between low-diversity microbiota and allergy development are emerging. The modulation of the intestinal microbiota can be done by a supplementation of probiotics and prebiotics. Thinking about strategies for modulating the intestinal microbiota through food, we can point to the Mediterranean diet, defined as a healthy and balanced diet. Final considerations: pediatric allergies that normally disappear with growth are becoming more present in adulthood. Nutritional techniques with probiotics, prebiotics and healthy diets such as the Mediterranean diet may be a promising target for preventive strategies against food allergies. However, we need more scientific evidence that can be translated into clinical practice.